An empirical analysis of the effects of macroeconomic variables on exchange rate: A time series analysis using ECM - Gunawan, Rudi; Khasanah, Uswatun; Shayo, Amani (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
There are increasing on debate about how the macroeconomic variables causes exchange rate. There are evidence that macroeconomic variables has a little evidence on exchange rate volatility and vice versa.  This study aims to analyze the impact of macroeconomic variables, namely exports, imports, inflation, money supply, and interest rates, on the Rupiah exchange rate using the Error Correction Model approach. Using monthly data from 2010 to 2023 obtained from the Central Bureau of Statistics and Bank Indonesia. The finding shows in the long run, exports have a negative effect on the exchange rate, while money supply and interest rates have a positive effect and indicates that an increase in these variables will strengthen the exchange rate. In the long run, imports and inflation do not show a significant effect in the long run. In the short run, only money supply and interest rates significantly affect the exchange rate, while exports, imports, and inflation do not. This study highlights the importance of understanding these macroeconomic dynamics for more effective economic policy making in Indonesia.  The dominant role of monetary policy over trade and price variables in stabilizing the exchange rate. Policymakers should focus on managing money supply and interest rates while promoting exports to maintain Rupiah stability amid global uncertainty.